LC–MS/MS determination of deoxyelephantopin, a novel anti-tumor candidate in rat plasma and its application to a pharmacokinetic study in rats - Niu,Kai (2018)
Abstract A specific, sensitive and robust LC–MS/MS method was developed and validated for the quantification of deoxyelephantopin in rat plasma using simvastatin as an internal standard as per regulatory guidelines of Bioanalytical Method Validation. Plasma sample was prepared through liquid-liquid extraction. Chromatographic separation was performed on an Agela-C18 analytical column (1.8 µm, 2.1 mm × 50 mm) with an isocratic mobile phase consisting of 0.05% formic acid (dissolved in acetonitrile) and water (55:45, v/v) at a flow rate of 0.5 ml/min. The column oven was maintained at 40 ºC and the injection volume was 4 µl. Elution of deoxyelephantopin and the internal standard occurred at 5.1 and 6.3 min, respectively. The total chromatographic run time was 7.5 min. A linear response function was constructed in the concentration range of 13.2–2640 ng/ml. The intra- and inter-day precision and accuracy were in the range of 1.4–14.8% and –11.7 to 14.1%, respectively. The validated LC–MS/MS was successfully applied to the pharmacokinetic study of deoxyelephantopin after intravenous injection of 1, 2 and 4 mg/kg and oral administration of 7.5, 15 and 30 mg/kg deoxyelephantopin in rats. After oral and intravenous administration, the C max and AUC values of deoxyelephantopin increased dose-dependently.